Chi ha paura della chimica? - Rollini, Ruggero; Tortorella, Sara (Chimica nella Scuola, 2024)
“Chemicals are like people – some are good, some are bad, and most are in between”. Unfortunately, chemicals perception in modern society is way more complex than this excellent metaphor. Chemophobia is one of the results of this complexity. By asking and answering direct questions as: What is it? When is it born? How bad is it? Why is it so pervasive? How to solve it? A systematic literature review on chemophobia has been carried out and its results are hereby reported. We hope this review will pave the way for a better understanding of the chemophobia phenomenon, and possible measures to contrast it.